Copper decorated perovskite an efficient catalyst for low temperature hydrogen production by steam reforming of glycerol - Ramesh, S.; Yang, Eun-Hyeok; Jung, Jae-Sun; Moon, Dong Ju (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Low temperature hydrogen production from stream reforming of glycerol is carried out over copper decorated perovskite catalysts under vapor phase reaction conditions. Among the catalysts studied LaNi0.9Cu0.1O3 showed the best performance with 73% glycerol conversion and 67% hydrogen selectivity. The chemical and structural properties of catalysts before and after the reaction were studied by X-ray diffraction, CO2-TPD and TPR, TGA, TEM and XPS. When the catalysts were reduced with H-2, perovskite structure decomposes to La2O3, Ni and Cu, Cu deposits on Ni nano particles were generated, thereby forming Cu/Ni nano catalysts. Cu decoration resulted in, higher reduction of active Ni species with moderate basicity, good catalytic activity which was further decreased with increase in Cu concentration. The catalyst (LaNi0.3Cu0.1O3) did not change any activity till 24 h in time-on-steam at 650 degrees C. TGA analysis revealed that copper decorated catalyst has better resistance to coke deposition compared to pervoskite catalysts. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: BIODIESEL BY-PRODUCT; RENEWABLE HYDROGEN; OXIDE CATALYSTS; ALKALINE-EARTH; METHANE; HYDROCARBONS; ISSUES; GAS; CU